2015
DOI: 10.1007/978-3-642-31395-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Petrological and Experimental Constraints on the Evolution of Piton de la Fournaise Magmas

Abstract: International audienceThis chapter outlines essential petrological features of Piton de la Fournaise magmas. The main characteristics of the different magma types, and of their components (mineral and glass phases) are detailed. The available geophysical and petrological informations on the structure of the feeding system are combined and the magmatic conditions (temperature, volatile concentrations, redox state) summarized. Experimental modelling of the magmatic evolution is limited by the presently available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Values as low as 0.1 K/min, however, are lower than the cooling rate imposed in the experiments (see viscometry data plotted in Fig− ure 1). We attribute this mismatch to the changes in oxygen fugacity between the experiments, carried out in atmospheric conditions, and the natural lava, being erupted in a more reduced state; see Vlastélic et al [2016], Pichavant et al [2016] and references therein. The pre− eruptive fO 2 for PdF magmas is estimated at ~NNO−0.5 and shallow level degassing of SO 2 and H 2 O might further KOLZENBURG ET AL.…”
Section: Implications For Magma Transport and Lava Emplacement At Pitmentioning
confidence: 99%
“…Values as low as 0.1 K/min, however, are lower than the cooling rate imposed in the experiments (see viscometry data plotted in Fig− ure 1). We attribute this mismatch to the changes in oxygen fugacity between the experiments, carried out in atmospheric conditions, and the natural lava, being erupted in a more reduced state; see Vlastélic et al [2016], Pichavant et al [2016] and references therein. The pre− eruptive fO 2 for PdF magmas is estimated at ~NNO−0.5 and shallow level degassing of SO 2 and H 2 O might further KOLZENBURG ET AL.…”
Section: Implications For Magma Transport and Lava Emplacement At Pitmentioning
confidence: 99%
“…The circle marked "b" is the average of the least degassed compositions from the Mariana arc (Brounce et al 2014). Panel b: This is constructed after Pichavant et al (2016), with olivine-liquid equilibrium constraints from Burgisser and Bachèlery (2009), bulk rock FeO and Fe 2 O 3 analyses from Burgisser et al (2015), and olivine-spinel equilibria from Burgisser et al (2015) and Bureau et al (1998b). The solid black line demonstrates the likely fO 2 of Reunion magmas during petrogenesis summarized by Pichavant et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Panel b: This is constructed after Pichavant et al (2016), with olivine-liquid equilibrium constraints from Burgisser and Bachèlery (2009), bulk rock FeO and Fe 2 O 3 analyses from Burgisser et al (2015), and olivine-spinel equilibria from Burgisser et al (2015) and Bureau et al (1998b). The solid black line demonstrates the likely fO 2 of Reunion magmas during petrogenesis summarized by Pichavant et al (2016). The pink box marked "this study" shows the fO 2 of least degassed magmas inferred here from XANES analyses of melt inclusions ◂ Although definitive links between each isotopic component and specific mantle source lithologies and their provenance are debated, it has been suggested that the EM1, EM2, and HIMU components reflect seafloor sediments, ancient oceanic and/or continental crust and/or lithospheric mantle, and perhaps surface lithologies not currently present at Earth's surface, recycled into the mantle by subduction and subsequently entrained into mantle plumes (e.g., Boyet et al 2019;Chauvel et al 1992;Cordier et al 2021;Garapic et al 2015;Hofmann and White 1982;Stracke et al 2005;Zindler and Hart 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg‐Fe distribution coefficients (K D ) between these ol and bulk rock composition are on average 0.24, which show that most of these ol are too rich in Mg considering our bulk rock composition (equilibrium reach at K D = 0.30 ± 0.03, Putirka, ). In order to calculate the FeO content of the cumulative ol‐free bulk rock composition (6.46 wt% in MgO and 10.16 wt% in FeO), we used an average Fe 3+ /Fe total ratio of 0.18 for La Réunion island basaltic melts (Pichavant et al, ). We thus conclude that most of these ol microphenocrysts originate from cumulative processes (22 analyzed crystals with Fo > 80), and only a few crystals are in equilibrium with the pre‐eruptive/bulk rock melt (six analyzed crystals with Fo 78‐80 ).…”
Section: Resultsmentioning
confidence: 99%